The Effects of Binding and Non-Binding Job Search Requirements - Patrick Arni; Amelie Schiprowski (Institute for the Study of Labor (IZA), 2015)
Job search requirements constrain the effort choice of unemployment insurance recipients by enforcing a minimum number of monthly applications. This paper is the first to assess how individual search effort, job finding and job stability react to this constraint. Standard job search theory predicts that requirements affect each job seeker relative to her unconstrained effort choice. Therefore, the behavioral treatment intensity of interest is the incremental effort necessary to comply with the requirement. Using novel Swiss register data, we measure this intensity as the difference between the individual requirement threshold and the search effort provided just before requirement imposition. Our econometric approach exploits that conditional on a broad set of choice fixed effects the match between the job seeker's unconstrained effort choice and the caseworker's requirement setting behavior is arbitrary. Therefore, it provides exogenous variation in the treatment assignment. We find that binding search requirements that exceed the job seeker's unconstrained effort choice, increase job finding in a substantial way. These effects are highly heterogeneous with respect to the job seeker's characteristics. They come at the cost of increased non-compliance and sanction imposition rates. Moreover, binding requirements have striking negative effects on job stability. Finally, we find that non-binding requirements can also affect search outcomes. This suggests that requirements can operate as signals, thereby generating behavioral effects that are not predicted by standard job search theory.
Keywords: J64; J65; 330; job search behavior; unemployment insurance; incentive effects